Phylogeny of the deep-sea cirripede family Scalpellidae (Crustacea, Thoracica) based on shell capitular plate morphology - Gale, A. S. (Zoological Journal of the Linnean Society, 2015)
A cladistic analysis of 23 extant species of the deep-sea pedunculate cirripede family Scalpellidae was undertaken, based on 61 shell plate characters, and taking the Jurassic–Cretaceous scalpellomorph genus Cretiscalpellum as an out-group. The consensus tree shows progressive morphological change from basal to more derived taxa, but a derived group is marked by major morphological innovation, including 27 character state changes that permit subdivision of the family into two sharply demarcated clades–the more basal group is here placed within a redefined Scalpellinae (Arcoscalpellum, Arcuatoscalpellum gen. nov., Diotascalpellum gen. nov., Graviscalpellum, Regioscalpellum gen. nov., and Scalpellum), and a more derived group named Amigdoscalpellinae subfam. nov. that shows numerous progressive trends in morphology, permitting the recognition of three genera (Amigdoscalpellum, Catherinum, and Weltnerium). The phylogeny is independently supported by a recently published multiple DNA marker-based molecular phylogeny. The more basal Scalpellinae appeared in the Aptian (Early Cretaceous, 120 Mya), and derived Amigdoscalpellinae were already present by the Campanian (Late Cretaceous, 78 Mya), represented by Catherinum anglicum sp. nov. and Amigdoscalpellum bellulum from the UK Chalk. Specialized receptacles to accommodate dwarf males in the apical interior of the scutum evolved at least three times during the history of the scalpellids.